If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+x+(2x-4)=26
We move all terms to the left:
2x+x+(2x-4)-(26)=0
We add all the numbers together, and all the variables
3x+(2x-4)-26=0
We get rid of parentheses
3x+2x-4-26=0
We add all the numbers together, and all the variables
5x-30=0
We move all terms containing x to the left, all other terms to the right
5x=30
x=30/5
x=6
| 66=(m+5)6 | | 5y-y+1/2=y-1/4+y | | 4(5-2x)=x-7 | | 4x^2+19x-140=0 | | 2y+6y-y=3 | | 4x²+19x-140=0 | | -1/4x2+3x+1=0 | | 25x2-10x+1=0 | | 8x2-9x+3=0 | | 5x2+25x=0 | | y-12=34 | | 7y=4y+5 | | -1x2+9=0 | | 4.6+x=8.9 | | 6x+4x-26=86 | | x-34=-3.2 | | x+1.8=-3.2 | | 1x2-81=0 | | 6x-24=86+4x | | 10x-13=5x-18 | | -x+16=-3x+4 | | 12x+3=5x+45 | | -3x-12=-x-32 | | 100x2=0 | | 7x+22=29 | | 2x-2=-2x-14 | | 14x-5+3x²=0 | | -8w+4(w+7)=32 | | 3x=80-2x | | (y+2)*4=64 | | 4(x-2)-3x=1.7 | | 5a+3=25 |